Innovation in the Introductions of the Ibn Al-Rumi,s Poems (283 AH - 896 AD) - Mousa Aziz, Aziz ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Ibn al-Rumi is regarded as one of the distinguished poets whose fame spread widely among his contemporaries. Although some critics described him as a satirist rather than a master of other types of poetry, through a close look at his poetry collection, we find that this judgment contains something of injustice, or a solitary judgment on the output of a poet who lived in an environment in which the elements of beauty and civilization were mixed with the diversity of intellectual and political schools of thought, making him a producer of a type of poem characterized by harsh, bitter satire. This research is an attempt to understand what is new in his poetry and to prove his poetic ability to keep pace with the development witnessed by his era, through an induction of his poetic texts that we subjected to a set of critical concepts by analyzing them in form and content. DOI: https://doi.org/10.54633/2333-024-056-013